PCSK9 (Proprotein Convertase Subtilisin Kexin Type 9) Inhibition in Hyperglycemic Mice Increases the Risk of Hemorrhagic Transformation of Ischemic Stroke. Issue 9 (September 2021) - Nativel, Brice; Ramin-Mangata, Stéphane; Couret, David; Planesse, Cynthia; Roche, Mathias; Gallo, Antonio; Meilhac, Olivier; Lambert, Gilles; Bourane, Steeve
Abstract : Supplemental Digital Content is available in the text.